2018
DOI: 10.1037/dev0000479
|View full text |Cite
|
Sign up to set email alerts
|

The role of identity commitments in depressive symptoms and stressful life events in adolescence and young adulthood.

Abstract: The formation of a stable identity, consisting of a strong set of commitments, is a key developmental task in adolescence and young adulthood. Not resolving this task and lacking strong identity commitments is related to difficulties like depressive symptoms and stressful life events. However, the exact role of identity commitments in these negative experiences has remained unclear. In two longitudinal studies in the Netherlands spanning 8 and 6 years, respectively, we examined the associations between career … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 64 publications
5
26
0
1
Order By: Relevance
“…Contrary to our expectation, we did not find evidence that the experience of a stressful event is related to change in identity (Tables 4 and 5). As such, our findings are partially consistent with an earlier study which revealed that stressful events were related to occupational, but not relational commitment, in adolescence (Van Doeselaar et al, 2018). However, our findings are inconsistent with studies on stressful events and identity in adulthood, which revealed decreases in commitment and increases in exploration and reconsideration within individuals following the occurrence of an event (e.g., Anthis, 2002).…”
Section: Identity and Stressful Life Eventssupporting
confidence: 69%
See 1 more Smart Citation
“…Contrary to our expectation, we did not find evidence that the experience of a stressful event is related to change in identity (Tables 4 and 5). As such, our findings are partially consistent with an earlier study which revealed that stressful events were related to occupational, but not relational commitment, in adolescence (Van Doeselaar et al, 2018). However, our findings are inconsistent with studies on stressful events and identity in adulthood, which revealed decreases in commitment and increases in exploration and reconsideration within individuals following the occurrence of an event (e.g., Anthis, 2002).…”
Section: Identity and Stressful Life Eventssupporting
confidence: 69%
“…This effect may be especially apparent in adolescence, a period characterized by development and transition (Lewin, 1939), as life events that occur during transitional periods are thought to have more or longer-lasting effects (Graber, Brooks-Gunn, & Peterson, 1996). The effect of life events on identity has as of yet received little empirical investigation in adolescence (however, see Van Doeselaar, Klimstra, Denissen, Branje, & Meeus, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a strong identity may protect adolescents from substance use. For instance, recent research showed that having strong commitments predicted fewer experienced stressful life events (Van Doeselaar et al, 2017). Therefore, having a strong identity may also protect adolescents from life stress-associated substance use.…”
Section: Linking Identity and Substance Usementioning
confidence: 99%
“…Consistent with this notion, identity issues, such as the inability to commit to an identity, have been associated with a range of indicators of poor psychosocial adjustment. For example, less committed individuals are more likely to report increased levels of internalizing and externalizing symptoms, and are more likely to reside in poorly functioning families (Crocetti et al, 2009;Schwartz et al, 2005;Van Doeselaar et al, 2017). Moreover, identity diffusion has been linked to substance use (Arnett, 2005;Schwartz et al, 2011).…”
mentioning
confidence: 99%
“…Consistent with this notion, identity disruption issues, such as the inability to commit to an identity, have been associated with a range of indicators of poor psychosocial adjustment. For example, less committed individuals are more likely to report increased levels of internalizing and externalizing symptoms, and are more likely to reside in poorly functioning families (Crocetti, Klimstra, Keijsers, Hale, & Meeus, 2009;Van Doeselaar, Klimstra, Denissen, Branje, & Meeus, 2017;Schwartz, Pantin, Prado, Sullivan, & Szapocznik, 2005). Moreover, identity diffusion has been linked to substance use (Arnett, 2005;Schwartz et al, 2011).…”
Section: Longitudinal Links Between Identity and Substance Use In Adomentioning
confidence: 99%